Does Integrated Social Spending and Zakat-Infaq-Sadaqah Improve Welfare in Indonesia? - Herlin, Herlin; Beik, Irfan Syauqi; Irfany, Mohammad Iqbal (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Human capital is widely acknowledged not only as a key driver of economic growth and poverty reduction but also as the ultimate objective of development, focused on expanding human freedoms. While government social spending is intended to achieve welfare objectives, it remains insufficient to fully finance public goods, necessitating alternative funding sources. Zakat, Infak, and Sedekah (ZIS) funds represent potential complementary resources, given their shared objective of promoting social welfare. This study aims to examine the role of integrated financing—social spending and ZIS—in enhancing human development in Indonesia. Using panel data from 34 provinces over the period of 2013–2022 and applying the System Generalized Method of Moments (Sys-GMM), the analysis evaluates both the independent and interactive effects of these funding sources. The findings reveal that social spending and ZIS individually exert a positive and significant effect on human development, while their integration produces a stronger and more substantial impact. These results highlight the importance of harmonizing Islamic social finance with state expenditures to accelerate human development outcomes. The study contributes to the literature as the first to apply a Sys-GMM approach in examining the interaction between social spending and ZIS, offering novel insights into the design of sustainable and inclusive development financing in Indonesia. Abstrak Apakah Integrasi Pengeluaran Sosial dan ZIS dapat Meningkatkan Kesejahteraan di Indonesia? Sumber daya manusia diakui tidak hanya sebagai pendorong utama pertumbuhan ekonomi dan pengentasan kemiskinan, tetapi juga sebagai tujuan akhir pembangunan yang berfokus pada perluasan kebebasan manusia. Meskipun pengeluaran sosial pemerintah ditujukan untuk mencapai tujuan kesejahteraan, alokasi tersebut belum cukup untuk sepenuhnya membiayai kebutuhan publik, sehingga diperlukan sumber pendanaan alternatif. Dana Zakat, Infak, dan Sedekah (ZIS) dipandang sebagai sumber daya pelengkap karena memiliki tujuan yang sama dalam meningkatkan kesejahteraan masyarakat. Penelitian ini bertujuan mengkaji peran pendanaan terintegrasi—pengeluaran sosial dan dana ZIS—dalam meningkatkan pembangunan manusia di Indonesia. Dengan menggunakan data panel dari 34 provinsi selama periode 2013–2022 serta pendekatan System Generalized Method of Moments (Sys-GMM), analisis dilakukan untuk mengevaluasi pengaruh langsung maupun interaksi dari kedua sumber dana tersebut. Hasil penelitian menunjukkan bahwa pengeluaran sosial dan dana ZIS masing-masing berpengaruh positif dan signifikan terhadap pembangunan manusia, namun ketika digabungkan, pengaruhnya menjadi lebih kuat dan substansial. Temuan ini menegaskan pentingnya harmonisasi antara keuangan sosial Islam dan belanja negara untuk mempercepat pencapaian pembangunan manusia. Penelitian ini berkontribusi sebagai studi pertama yang menerapkan Sys-GMM dalam menganalisis interaksi antara pengeluaran sosial dan ZIS, sekaligus memberikan wawasan baru mengenai perancangan pembiayaan pembangunan berkelanjutan dan inklusif di Indonesia.